2014
DOI: 10.1038/tpj.2014.67
|View full text |Cite
|
Sign up to set email alerts
|

High frequency and founder effect of the CYP3A4*20 loss-of-function allele in the Spanish population classifies CYP3A4 as a polymorphic enzyme

Abstract: Cytochrome P450 3A4 (CYP3A4) is a key drug-metabolizing enzyme. Loss-of-function variants have been reported as rare events, and the first demonstration of a CYP3A4 protein lacking functional activity is caused by CYP3A4*20 allele. Here we characterized the world distribution and origin of CYP3A4*20 mutation. CYP3A4*20 was determined in more than 4000 individuals representing different populations, and haplotype analysis was performed using CYP3A polymorphisms and microsatellite markers. CYP3A4*20 allele was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 22 publications
5
33
0
3
Order By: Relevance
“…We found one patient carrying the CYP3A4*20 allele (0.3%), a frequency similar to that found in a previous study recently performed by our group and lower than that reported previously by Apellániz‐Ruiz et al . . The only patient in our cohort who carried the CYP3A4*20 variant was also heterozygous (*1/*28) for UGT1A1 .…”
Section: Discussionmentioning
confidence: 70%
“…We found one patient carrying the CYP3A4*20 allele (0.3%), a frequency similar to that found in a previous study recently performed by our group and lower than that reported previously by Apellániz‐Ruiz et al . . The only patient in our cohort who carried the CYP3A4*20 variant was also heterozygous (*1/*28) for UGT1A1 .…”
Section: Discussionmentioning
confidence: 70%
“…The 9 variants studied were CYP3A4 *20 (rs67666821), CYP3A4 *22 (rs35599367), CYP3A5 *3 (rs776746), ABCB1 C3435T (rs1045642), ABCB1 C1236T (rs1128503), ABCB1 G2677T/A (rs2032582), OPRM1 A118G (rs1799971), COMT G472A (rs4680) and ADRB2 C523A (rs1042718), which were all genotyped by real‐time PCR using a StepOne ® PCR Instrument (Applied Biosystems, CA, USA) and TaqMan assays following the manufacturer recommendations (Applied Biosystems, CA, USA), except for CYP3A4 *20, which was genotyped using KASPar SNP Genotyping System (LGC Genomics, Herts, UK). The Sequence Detection System ABI PRISM 7900HT (Applied Biosystems, Darmstadt, Germany) was used for fluorescence detection and allele assignment …”
Section: Methodsmentioning
confidence: 99%
“…The Sequence Detection System ABI PRISM 7900HT (Applied Biosystems, Darmstadt, Germany) was used for fluorescence detection and allele assignment. 31…”
Section: Genotypingmentioning
confidence: 99%
“…One such example is the prevalence of the reduced functionality allele CYP2C8*2, which is not found in individuals of European or East Asian ancestry but is common in Africans (MAF = 15.9%) [7]. Similarly, the loss-of-function CYP3A4*20 allele causing increased risk of adverse reactions to, e.g., paclitaxel, was not found in Asian, African, South American, and most European populations but reached frequencies of 3.8% in specific regions of Spain [86]. Combined, these findings suggest that ethnic origin is an important parameter in pharmacogenomic research and understanding of the geographical distribution of genetic variability builds the fundament for precision public health approaches.…”
Section: Rare Genetic Variants and Population-specificitymentioning
confidence: 99%